Two new species of Dictyosporium from India - and N. KRISHNA RAO, C. MANOHARACHARY*, I.K. KUNWAR, (Indian Phytopathology, 2007)
Survey of microfungi from diversified habitats yielded two novel dematiaceous hyphomycetes belonging to Dictyosporium, collected from a forest near Gundlabrahmeswaram, Andhra Pradesh. These fungi differ from the documented species of Dictyosp.orium in size, shape, number of branches and number of cells in each branch, hence described as new species viz. Dictyosporium dkagarwalii sp. novo and D. tnlakhanpalii sp. novo.